2009
DOI: 10.1159/000236082
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Approach in Children with Short Stature

Abstract: For early detection of pathological causes of growth failure proper referral criteria are needed, as well as a thorough clinical, radiological and laboratory assessment. In this minireview we first discuss the two consensus-based and one evidence-based guidelines for referral that have been published. The evidence-based guidelines result in a sensitivity of approximately 80% at a false-positive rate of 2%. Then, relevant clues from the medical history and physical examination are reviewed, and specific investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
89
1
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(96 citation statements)
references
References 90 publications
0
89
1
6
Order By: Relevance
“…There are some published guidelines for the evaluation of short stature [12,13,14,15]. Our study has shown that adherence to these guidelines in the primary clinics referring children to our unit is only partial.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…There are some published guidelines for the evaluation of short stature [12,13,14,15]. Our study has shown that adherence to these guidelines in the primary clinics referring children to our unit is only partial.…”
Section: Discussionmentioning
confidence: 68%
“…The office evaluation of short stature made by the primary care physician represented in the referral letter was compared to acceptable short stature evaluation guidelines [12,13,14,15]. We noted whether the office evaluation included parental height, Tanner stage of puberty, previous growth data (or growth curves), and laboratory investigations including: complete blood count (CBC), erythrocyte sedimentation rate (ESR), serum electrolytes, concentration of blood urea nitrogen (BUN), creatinine, thyroid-stimulating hormone, free T 4 , IGF-1, celiac disease antibody panel, urinalysis, and bone age X-ray.…”
Section: Methodsmentioning
confidence: 99%
“…In approximately 80% of children who are referred to a pediatric clinic because of short stature, no definite cause can be established, even after a thorough diagnostic workup including extensive biochemical screening and radiologic investigations [1,2,3,4]. Such children are usually classified as idiopathic short stature (ISS) [1].…”
Section: Introductionmentioning
confidence: 99%
“…The European Society for Paediatric Endocrinology classification distinguishes between primary and secondary growth disorders and idiopathic short stature (ISS). 3 Primary growth disorders include clinically-defined syndromes such as Turner's and Cornelia de Lange, children who are small for gestational age (SGA) with failure to catch up, and skeletal dysplasias. Secondary growth disorders include malnutrition, disorders in organ systems (e.g.…”
Section: Conditions Related To Short Staturementioning
confidence: 99%